Landscape and Environment in Colonial and Postcolonial Africa. - Falola, Toyin (Routledge African studies., 2011)
This volume seeks to identify and examine two categories of colonial and postcolonial knowledge production about Africa. These two broad categories are ""environment"" and ""landscape, "" and both are useful and problematic to explore. Discussions about African environments often concentrate on Africans as perpetrators of their own land, causing degradation from lack of knowledge and technology. ""Landscape"" defines the category of knowledge produced by foreigners about Africa, where Africans remain part of the scenery and yield no agency over their surroundings. To flesh out these categories.